Who has Standing to Sue the President Over Allegedly Unconstitutional Emoluments? - Matthew Hall (Washington University Law Review, 2017)
Two provisions of the U.S. Constitution that have received comparatively little public attention over the past 227 years are suddenly all over the news, having provided the basis for three pending lawsuits against the president of the United States. The Foreign and Domestic Emoluments Clauses arose out of the Founders’ concern with corruption – in particular with the corrupting effects of gifts, payments, or benefits conferred on federal office holders either by foreign governments or their agents, or by any of the states constituting the United States. The founders viewed the risk of corruption stemming from such payments as so serious that they included in the text of the Constitution itself two clauses prohibiting the receipt of such benefits. The Foreign Emoluments Clause prohibits the receipt of gifts or other benefits from any foreign power, by any officer of the United States, without Congress’s express consent. The Domestic Emoluments Clause provides that the president’s salary shall remain fixed during his term, and that the president cannot receive any emolument other than his statutory salary, from any state government or any part of the federal government, during his term of office.
Keywords: Foreign and Domestic Emoluments Clauses; CREW v. Trump; Constitutional law